Effect of different memristor window function with variable random resistance on the performance of memristor-based RO-PUF - Loong J.T.H.; Ismail K.A.S.C.; Hamid F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Resistors; Systems engineering; Aliasing; Applied voltages; High operating frequency; Initial resistance; Memristor; Physically unclonable functions; Window functions; Memristors